Patogenia de la infección por SARS-CoV-2 - Faúndes G, Nicolás; Genskowsky V, Karen; Tordecilla F, Rocío (Revista Hospital Clínico Universidad de Chile, 2021)
Covid-19 is an infectious disease whose etiological agent called SARS-CoV-2. It has a high contagion rate, high morbidity and mortality, and potential multi-organ compromise. Its main route of infection is by droplets, however, the infection can be acquired by other routes such as aerosols, fecal-oral and contact with fomites. Although the immune response is essential for defense against any infection, in severe Covid-19 infection, a dysregulation of the immune system occurs, which leads to marked increases of cytokines and the consequent systemic inflammatory state. Inflammation, infection, and viral shedding can compromise the lungs, blood vessels, brain, gastrointestinal (GI) tract, kidneys, heart, and liver, ultimately leading to multiple organ dysfunction and failure.